Correlation of Serum Lipoproteins with the Activity of Acute Lymphoblastic Leukaemia - Al-Zubaidy, Azher Sebieh (AL-Kindy College Medical Journal, 2019)
Background: the activity of acute lymphoblastic leukemia had been observed to correlate with levels of serum lipoproteinsObjective: to evaluate the correlation of serum levels of different types of lipoproteins with activity of the disease in patients with acute lymphoblastic leukemia.Type of the study: A prospective study.Methods: A study included patients diagnosed as acute lymphoblastic leukemia, their serum levels of lipoproteins at time of diagnosis, and on relapse were obtained for comparison.Results: there is significant inverse correlation of activity of acute lymphoblastic leukemia with serum total cholesterol, serum low density cholesterol levels, and serum high density lipoprotein level, but not with serum triglycerides level.Conclusion:. The level of lipid profile is inversely correlated with activity of acute leukemia, and lipid profile assessment is recommended in evaluation of patients with acute leukemia .